2022
DOI: 10.3390/life12020174
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of C1GALT1 Enhances the Progression of Cholangiocarcinoma through Activation of AKT/ERK Signaling Pathways

Abstract: Alteration of mucin-type O-glycosylation is implicated in tumor progression and metastasis of cholangiocarcinoma (CCA). Core 1 β1-3 Galactosyltransferase (C1GALT1) is a primary enzyme that regulates the elongation of core 1-derived mucin-type O-glycans. Dysregulation of C1GALT1 has been documented in multiple cancers and is associated with aberrant core 1 O-glycosylation and cancer aggressiveness; however, the expression of C1GALT1 and its role in CCA progression remains unknown. Our study demonstrated that C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In 2015, Hofmann and colleagues demonstrated that the knockdown of the COSMC chaperone, preventing O -glycan elongation beyond the initial GalNAc α 1- residue on O -linked glycoproteins [ 31 ], was associated with elevated migration and reduced apoptosis of pancreatic cancer cells, suggesting that such a simple O -linked glycan may modulate the survival of transformed cells [ 31 ]. Recently, it has been revealed that the down-regulation of C1GALT1 in cholangiocarcinoma (CCA) promoted the expression of immature core 1 O -glycan, enhancing CCA progression, which was associated with the up-regulation of ABC transporter genes and anti-apoptotic proteins [ 32 ], which are both effects associated with the emergence of MDR phenotypes. In addition, C1GALT1 knockdown cells showed resistance to 5-fluorouracil via the activation of the AKT/ERK signaling pathway [ 32 ].…”
Section: Unusual O -Linked Glycan Structures and T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Hofmann and colleagues demonstrated that the knockdown of the COSMC chaperone, preventing O -glycan elongation beyond the initial GalNAc α 1- residue on O -linked glycoproteins [ 31 ], was associated with elevated migration and reduced apoptosis of pancreatic cancer cells, suggesting that such a simple O -linked glycan may modulate the survival of transformed cells [ 31 ]. Recently, it has been revealed that the down-regulation of C1GALT1 in cholangiocarcinoma (CCA) promoted the expression of immature core 1 O -glycan, enhancing CCA progression, which was associated with the up-regulation of ABC transporter genes and anti-apoptotic proteins [ 32 ], which are both effects associated with the emergence of MDR phenotypes. In addition, C1GALT1 knockdown cells showed resistance to 5-fluorouracil via the activation of the AKT/ERK signaling pathway [ 32 ].…”
Section: Unusual O -Linked Glycan Structures and T...mentioning
confidence: 99%
“…Recently, it has been revealed that the down-regulation of C1GALT1 in cholangiocarcinoma (CCA) promoted the expression of immature core 1 O -glycan, enhancing CCA progression, which was associated with the up-regulation of ABC transporter genes and anti-apoptotic proteins [ 32 ], which are both effects associated with the emergence of MDR phenotypes. In addition, C1GALT1 knockdown cells showed resistance to 5-fluorouracil via the activation of the AKT/ERK signaling pathway [ 32 ]. One of the glycoconjugates that are directly affected by overexpression of the STn antigen is MUC1.…”
Section: Unusual O -Linked Glycan Structures and T...mentioning
confidence: 99%
“…Through the regulation of protein stability, subcellular localization, activity, and interactions, glycosylation plays a wide-ranging role in key cellular processes, including gene transcription, cell cycle regulation, DNA repair, apoptosis, virus budding, receptor endocytosis, and various physiological and pathological processes ( 16 18 ). Tumor cells exhibit extensive glycosylation changes compared to untransformed cells, and glycosylation has been closely associated with various cancers, including hepatocellular cancer ( 19 21 ), pancreatic cancer ( 22 , 23 ), gastric cancer ( 24 ), bladder cancer ( 25 ), breast cancer ( 21 ), esophageal cancer ( 26 ), cholangiocarcinoma ( 27 ) etc. In colorectal cancer (CRC), glycosylation can impact cell migration, intercellular adhesion, actin polymerization, mitosis, cell membrane repair, apoptosis, cell differentiation, stem cell regulation, intestinal mucosal barrier integrity, immune system regulation, T cell polarization, and intestinal microbiota composition ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of tumor-associated O-linked glycosylation includes Core 1 β1-3 galactosyltransferase (C1GALT1), C1GALT1-specific chaperone (COSMC), Core 2 β1,6-N-acetylglucosaminyltransferase-1 (C2GNT1), Core 2 β1,6-N-acetylglucosaminyltransferase-2 (C2GNT2), and Core 3 β1,3-N-acetylglucosaminyltransferase 6 (B3GNT6) ( Curigliano et al, 2020 ; Martinez-Saez, Peregrina & Corzana, 2017 ; Miyamoto et al, 2013 ; Okamoto et al, 2013 ; Schachter & Brockhausen, 1989 ; Sindrewicz, Lian & Yu, 2016 ). Down-regulation of C1GALT1 and its chaperone, COSMC, contributed to increased truncation of O-glycans, Tn and sialyl-Tn (sTn) antigens, on mucin glycoproteins ( Chugh et al, 2018 ; Khiaowichit et al, 2022 ; Liu et al, 2020 ; Sagar et al, 2021 ). C2GNT1 competes with ST3 β-galactoside α-2,3-sialyltransferase 1 (ST3GAL1) and further truncated O-glycosylation by capping the T-antigen with sialic acid ( Chandrasekaran et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%